Prevalence, Molecular Characterization, and Antimicrobial Resistance Profile of Enterotoxigenic Escherichia coli Isolates from Pig Farms in China - Jiajia Zhu; Zewen Liu; Siyi Wang; Ting Gao; Wei Liu; Keli Yang; Fangyan Yuan; Qiong Wu; Chang Li; Rui Guo; Yongxiang Tian; Danna Zhou (Foods)
Enterotoxigenic Escherichia coli (ETEC) poses a critical threat to livestock health and food safety, particularly in regard to misuse of antimicrobial agents, which have accelerated the evolution of multidrug-resistant (MDR) ETEC strains, reshaping their virulence landscapes and epidemiological trajectories. In this study, 24 ETEC isolates from porcine diarrheal samples undergo genomic and phenotypic profiling, including virulence genotyping, bacterial adhesion, and antimicrobial resistance (AMR) analysis. Results show that multi-locus sequence typing (MLST) outputs (ST88, ST100) and serotypes (O9:H19, O116:H11, O149:H10) exhibited enhanced virulence, with F18ab-fimbriated strains carrying Shiga toxin genes (stx2A) demonstrating higher cytotoxicity than non-stx strains. There exists a significant negative correlation between bacterial growth rates and intestinal epithelial adhesion, with the expression of ETEC adhesion and virulence genes being growth-time-dependent. These relationships suggest evolutionary trade-offs favoring either rapid proliferation or virulence. Among these isolates, 95.8% were MDR, with alarming resistance to quinolones and aminoglycosides. Geospatial analysis identified region-specific AMR gene clusters, notably oqxB-aac(3) co-occurrence networks in 79% of ETEC isolates. These results highlight the urgent need for precision interventions, including vaccines targeting epidemic serotypes and AMR monitoring systems to disrupt resistance propagation across swine production networks. By underscoring the importance of current virulence and AMR profiles, this study provides actionable strategies to mitigate ETEC-associated threats to both animal welfare and meat safety ecosystems.